Effective interventions for gaming disorder: A systematic review of randomized control trials - Chen, Yuzhou; Lu, Jiangmiao; Wang, Ling; Gao, Xuemei (Frontiers in Psychiatry, 2023)
Objective To identify effective intervention methods for gaming disorder (GD) through a rigorous assessment of existing literature. Methods We conducted a search of six databases (PubMed, Embase, PsycINFO, CNKI, WanFang, and VIP) to identify randomized controlled trials (RCTs) that tested GD interventions, published from database inception to December 31, 2021. Standardized mean differences with 95% confidence intervals were calculated using a random effects model. Risk of bias was assessed with the Risk of Bias 2 (RoB 2) tool. Results Seven studies met the inclusion criteria. Five interventions were tested in these studies: group counseling, craving behavioral intervention (CBI), transcranial direct current stimulation (tDCS), the acceptance and cognitive restructuring intervention program (ACRIP), and short-term cognitive behavior therapy (CBT). Four of the five interventions (the tDCS was excluded) were found to have a significant effect on GD. The results of the quality assessment showed that the included studies had a medium to high risk in the randomization process and a medium to high risk of overall bias. Conclusion Rigorous screening identified that four interventions are effective for GD: group counseling, CBI, ACRIP, and short-term CBT. Additionally, a comprehensive review of the literature revealed that improvements could be made in the conceptualization of GD, experimental design, sample representativeness, and reporting quality. It is recommended that future studies have more rigorous research designs and be based on established standards to provide more credible evidence to inform the development of GD interventions.